Working Paper Summaries (WP/94/77 - WP/94/147). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
Authors of Working Papers are normally staff members of the Fund or consultants, although on occasion outside authors may collaborate with a staff member in writing a paper. The views expressed in the Working Papers or their summaries are, however, those of the authors and should not necessarily be interpreted as representing the views of the Fund. Copies of individual Working Papers and information on subscriptions to the annual series of Working Papers may be obtained from IMF Publication Services, International Monetary Fund, 700 19th Street, Washington, D.C. 20431. Telephone: (202) 623-7430 Telefax: (202) 623-7201 This compilation of summaries of Working Papers released during July-December 1994 is being issued as a part of the Working Paper series. It is designed to provide the reader with an overview of the research work performed by the staff during the period.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet